ENTREPRENEURSHIP, A SOLUTION TO IMPROVE YOUTH EMPLOYMENT IN THE EUROPEAN UNION - Mariana-Cristina, GANESCU (Strategii Manageriale)
The high level of unemployment among young people in EU countries reflects the difficulties young people face in finding a job. On the premise that entrepreneurship is a solution to youth unemployment in the European Union, the present study uses the entrepreneurial ecosystem assessment methodology proposed by the Global Entrepreneurship and Development Institute. Panel data analysis reveals a negative correlation between the level of development of the entrepreneurial ecosystem and the level of youth unemployment. The paper is of interest because it emphasizes the idea that a high level of development of the entrepreneurial ecosystem may reduce the level of youth unemployment.